INVASION OF THE THIARID SNAIL Melanoides tuberculata (MOLLUSCA) IN A CONSERVATION AREA OF THE SEMIARID REGION OF BRAZIL (Environmental Smoke, 2023)
This paper records the invasive gastropod Melanoides tuberculata in a limnetic ecosystem located in integral protection area in the semiarid region of the state of Paraíba in northeast Brazil. Live individuals were collected and photographed along shallow margins of the Piranhas Reservoir associated with different types of substrates. Photographic quadrants were used to calculate the number of living individuals and empty shells on different substrates. Individuals of M. tuberculata were found at five sampling sites in the littoral zone on different types of substrates with densities ranging of 13 ind.(m2)-1 to 22 ind.(m2)-1. The average density of individuals was: 18 ind.(m2)-1 on thin sediment, 15 ind.(m2)-1 on gravel and 20 ind.(m2)-1 on rocks. Empty shells were extremely abundant in the terrestrial zone of the reservoir. We did not observe native species of freshwater molluscs in the marginal areas of the reservoir in which the specimens of M. tuberculata were found. Knowledge about the distribution, establishment and impact caused of M. tuberculata in limnetic ecosystems of the Brazilian semi-arid region needs to be better studied in order to ascertain the degree of impact on native species and environmental modifications that reflect negatively on ecosystems.